Pinoy teen connect! designing a filipino-teen Christian radio magazine program for 104.3 Edge radio Davao - Otagan, Minsei Shaira C.
This study sought to formulate and design an original Filipino-Christian oriented radio magazine program format for 104.3. The Edge Radio Davao. The study aims to address the radio station?s dilemma in effectively relating and gaining more positive feedbacks from their target audiences considering their current materials and radio programming in the city. The Uses and Gratification theory, especially the concept of audience side from McQuail?s Integrated Model of Audience Choice were employed in the study, which mainly focus on audience?s preferences and their power to control of media. The new program aims to address and combine radio station?s programming preferences and the radio listening preferences of the radio station?s specified target audience, which are the Filipino-Christian teenagers in Davao City. To identify the target audience?s general set of Christian radio content preferences, the researcher have used a primary audience research which included both quantitative and qualitative methods. Research survey questionnaires were utilized in the study. The sample comprised 250 Filipino-Christian teenagers who are 12-19 years old from different areas in Davao city. Majority of the respondents are Protestants. The radio magazine program?s format as well as its content is mainly based on the results of the audience research. The findings showed that in general, the respondents prefer the following Christian program content over the others such as, (1) Talk shows on love and relationships, and family, (2) Short radio shows on Bible stories, parables and verses; and (3) features about Christian music. Issues about Education, Health and Relationships are also shown to be the three most important topics for the respondents prefer Christian radio drama as one of the content in a Christian radio program. Findings also show that majority of the respondents prefer Tagalog as the main broadcasting language for the radio station over English, Bisaya, and other dialects. Moreover, majority of the respondents tend to listen to radio longer during Sundays from 30 minutes to three hours, before 6:00AM and after 6:00PM compared to the other days of the week. These results show us patterns of the listening habits and preferences of the target subjects in the study. The results from audience research as well as some guidelines on radio programming aided the researcher in the production of the new radio magazine format for the subject radio station. The production of the program segments, conclusions derived from the study, recommendations and further considerations for future research are also discussed.